Type 2 Diabetic Patients’ Knowledge Regarding Preventive Measures of Diabetic Foot - sabah, shahad (Iraqi National Journal of Nursing Specialties, 2022)
Objective: Assess type 2 diabetic patients’ knowledge regarding preventive measures of diabetic foot. Find out the relationship between of type 2 diabetic patients’ knowledge regarding preventive measures of diabetic foot with certain sociodemographic characteristics Methodology: A descriptive study was carried out from (2nd January 2022 to 26th March 2022). A non –probability (purposive) sample of (60) adult patients who are diagnosed with type2 diabetes mellitus these patients have met the study criteria which was selected from Imam AL-Hussein Medical-City. The study instrument consist of two section: (Demographic Information Sheet, and Foot Care Outcome Expectations Scale) The questionnaire was designer measure the level of diabetic patient’ knowledge about preventive measures of diabetic foot, which consisted of (14) items and other structured knowledge questionnaire containing (6) questions were developed by researcher based on the existing resources to assess knowledge of patient regarding preventive measures of diabetic foot. Results: The study indicates that the patient have fair level of knowledge (MS=1.34), and no significant association between diabetic Patients’ Knowledge Regarding Preventive Measures of Diabetic Foot and their demographic characteristics. Conclusion: The results show that the level of knowledge about preventive measures for the diabetic foot of the patients was Fair. There are no significant differences were found regarding demographic variables. Recommendations: The Ministry of Health should use the media to organize public health campaigns to strengthen knowledge towards contributing factors and preventive measures for diabetic foot. Further research is recommended to repeat the research on a large probability sample to achieve further generalization.